Myxoid Fibroadenoma of the Breast: A Rare Histological Variant Case Report and Literature Review - Abdullah S. Al-Darwish; Hisham AlKhalidi; Hammad Akram; Nuha A. Alsaleh (Dr. Sulaiman Al Habib Medical Journal)
Breast myxoid fibroadenoma (MFA) is a rare entity characterized by hypocellular myxoid stroma and is either sporadic or associated with the Carney complex, an inherited disorder caused by PRKAR1A-inactivating germline mutations. Here, we present the case of a 17-year-old girl who presented with a 3-cm mass in her left breast, suggestive of fibroadenoma. The mass was surgically excised, and histopathology revealed MFA. We sought to review breast MFA and compare it to conventional fibroadenoma.